Attitudes, practices, and priority of HIV screening and testing among clinical providers in Transylvania and Moldavia, Romania - Cabiria M. Barbosu; Amanda Radulescu; Carmen Manciuc; Erin Muir; Brooke A. Levandowski; Timothy Dye (BMC, 2019)
Abstract Screening and linkage to care are core, foundational strategies for HIV transmission prevention and for identifying People Living with HIV (PLHIV). In Romania - with an atypical experience in the HIV/AIDS epidemic - providing care for HIV+ patients identified early is a priority, though screening and testing can pose a challenge in some areas. Methods A survey of 125 clinical providers to explore important dimensions of HIV/ AIDS clinical care was conducted in Transylvania and Moldavia, where clinicians identified poor/ latent screening as a major problem in providing timely care and in preventing the spread of disease. We analyzed determinants of offering HIV screening/testing to patients using Pearson Chi-square analysis and logistic regression. Logistic regression generated Odds Ratios (OR) to reflect the magnitude of association between the relevant variables, with 95% confidence interval (95% CI) indicating statistical range. Results In total, 40.8% of providers did not provide HIV screening/testing to at least one segment of the population. Hospital-based providers were significantly more likely to offer HIV screening/testing to all segments than were non-hospital-based providers (58.1% v. 35.5%, respectively; p < .05). Providers located within institutions with screening/testing policies were more likely to offer such services to their patients (p < .05). Overall, 94.4% of providers indicated interest in more training around HIV screening/testing. Discussion Reaching Romanian and global goals for reducing HIV require more timely screening and action based on positive status. Romanian clinicians are interested in expanding HIV screening/testing and are interested in participating in training that helps them feel more prepared to undertake this work.